2022
DOI: 10.1186/s40793-022-00428-y
|View full text |Cite
|
Sign up to set email alerts
|

Methanol utilizers of the rhizosphere and phyllosphere of a common grass and forb host species

Abstract: Background Managed grasslands are global sources of atmospheric methanol, which is one of the most abundant volatile organic compounds in the atmosphere and promotes oxidative capacity for tropospheric and stratospheric ozone depletion. The phyllosphere is a favoured habitat of plant-colonizing methanol-utilizing bacteria. These bacteria also occur in the rhizosphere, but their relevance for methanol consumption and ecosystem fluxes is unclear. Methanol utilizers of the plant-associated microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…The methanol-enriched wheat rhizosphere soils exclusively contained MAGs identified as Gemmatimonadales, Roseimicrobium and Nitrososphaeraceae. This supports the prior identification of a greater diversity of these specific taxa in the methanolenriched rhizosphere soils relative to the unplanted soils (Macey et al, 2020), with many of the taxa previously identified as enriched in rhizosphere soils (e.g., Chthoniobacter [Sangwan et al, 2004], Nitrososphaeraceae [Prudence et al, 2021], Methylophilaceae [Kanukollu et al, 2022;Macey et al, 2020], and species within the Acidobacteriota and Verrucomicrobiota [Da Rocha et al, 2013;Lanzavecchia et al, 2024]).…”
Section: Ensemble and Direct Binning Approachessupporting
confidence: 82%
“…The methanol-enriched wheat rhizosphere soils exclusively contained MAGs identified as Gemmatimonadales, Roseimicrobium and Nitrososphaeraceae. This supports the prior identification of a greater diversity of these specific taxa in the methanolenriched rhizosphere soils relative to the unplanted soils (Macey et al, 2020), with many of the taxa previously identified as enriched in rhizosphere soils (e.g., Chthoniobacter [Sangwan et al, 2004], Nitrososphaeraceae [Prudence et al, 2021], Methylophilaceae [Kanukollu et al, 2022;Macey et al, 2020], and species within the Acidobacteriota and Verrucomicrobiota [Da Rocha et al, 2013;Lanzavecchia et al, 2024]).…”
Section: Ensemble and Direct Binning Approachessupporting
confidence: 82%
“…Nevertheless, we acknowledge that the specific coupling pathways of CH 4 oxidation and denitrification may vary among different strains and within diverse microbial communities. For instance, the results from 13 CH 4 -SIP indicate that Rhizobia , as carriers of denitrification gene nirK , have the potential to utilize C from CH 4 , but with specific metabolic pathways remaining unclear 50 , 51 . Therefore, additional studies, such as isolating these specific taxa in pure culture and utilizing third-generation metagenomic approaches to obtain higher quality MAGs, are warranted to reinforce and consolidate the findings presented in this study.…”
Section: Discussionmentioning
confidence: 99%